Empirical Analysis of Farmers Household Food Security Levels in Salatiga, Indonesia - Ariyadi, Wahyu (Research Horizon, 2021)
This study aims to analyze the conditions of farm household food security levels and analyze the magnitude of the influence of factors such as farmer income, farmer education, farmer age, and number of family members on the level of food security of farm households in Sidorejo District, Salatiga City. This study uses data taken by survey methods and interviews with farmers as respondents. The number of samples used was 90 respondents, taken using the simple random sampling method in Pulutan Village, Kauman Kidul Village, and Blangkas Village as the areas where surveys and interviews were conducted with the largest number of farmer households registered in the Farmer Members Group in Sidorejo District. Data were analyzed using qualitative descriptive analysis, multiple linear regression analysis with the Ordinary Least Square (OLS) method, and the use of a proportion of food expenditure as an indicator for the level of food security of farm households. The analysis showed that statistically the factors of farmer income, farmer education, and the number of family members of the farmer had a significant effect on the level of food security of the household of the farmer, while the age factor of the farmer had no significant effect. Many as 55.56% of households have a proportion of food expenditure ≥ 60% or food insecurity. The rest, as much as 44.44% of households have food expenditure <60% or food security. Based on these results, the advice given is to increase farmers’ incomes by providing skills and training, as well as dissemination of policies on Sustainable Food Home Areas (KRPL).